Calotropis gigantea Leaf Extract Increases the Efficacy of 5-Fluorouracil and Decreases the Efficacy of Doxorubicin in Widr Colon Cancer Cell Culture - Roihatul Mutiah, Aty Widyawaruyanti & , Sukardiman Sukardiman (Journal of Applied Pharmaceutical Science, 2018)
Colon cancer is a malignant neoplasm with high incidence and causes the death of more than 30% of the patients. Although there have been efforts to increase the life of the patient using chemotherapy agents, unspecified targets of drugs cause serious side effects and lead to multiple drug resistance (MDR). This is a major problem in cancer therapy in general. Efforts to use substances from plants that have low toxicity give new hope as a co-chemotherapy agent that can increase the efficacy of chemotherapy agents and reduce their toxicity to normal cells. This study aimed to determine the synergistic effects of therapy combination of Calotropis gigantea (EDCG) leaf extract with the chemotherapy drug 5-Fluorouracil (5-FU) and doxorubicin against WiDR colon cancer cells. The analysis results of MTT showed that the combination of EDCG and 5-Fluorouracil gives synergism effect at the dose combination of EDCG+5FU (3 μg/ml + 62.5 nM; 3 μg/ml + 125 nM; 3 μg/ml + 250 nM). While the combination of doxorubicin and EDCG creates antagonistic effects of mild to the strong antagonist, EDCG may enhance the efficacy of 5 Fluorouracil but decrease the efficacy of doxorubicin. Therefore, a combination of EDCG and 5-Fluorouracil may be recommended for further study.
Keywords: Calotropis gigantea, 5-Fluorouracil, doxorubicin, co-chemotherapy, WiDr cell.